Oral Elesclomol Treatment Alleviates Copper Deficiency in Animal Models - Yuan, Sai; Korolnek, Tamara; Kim, Byung-Eun (Frontiers in Cell and Developmental Biology, 2022)
Copper (Cu) is an essential trace element for key biochemical reactions. Dietary or genetic copper deficiencies are associated with anemia, cardiomyopathy, and neurodegeneration. The essential requirement for copper in humans is illustrated by Menkes disease, a fatal neurodegenerative disorder of early childhood caused by mutations in the ATP7A copper transporter. Recent groundbreaking studies have demonstrated that a copper delivery small molecule compound, elesclomol (ES), is able to substantially ameliorate pathology and lethality in a mouse model of Menkes disease when injected as an ES-Cu2+ complex. It is well appreciated that drugs administered through oral means are more convenient with better efficacy than injection methods. Here we show, using genetic models of copper-deficient C. elegans and mice, that ES supplementation through the diet fully rescues copper deficiency phenotypes. Worms lacking either the homolog of the CTR1 copper importer or the ATP7 copper exporter showed normal growth and development when fed ES. Oral gavage with ES rescued intestine-specific Ctr1 knockout mice from early postnatal lethality without additional copper supplementation. Our findings reveal that ES facilitates copper delivery from dietary sources independent of the intestinal copper transporter CTR1, and provide insight into oral administration of ES as an optimal therapeutic for Menkes disease and possibly other disorders of copper insufficiency.